Describing Injustice: Adverbs in “To Kill a Mockingbird” - I Gede Madriana; I Made Juliarta (Universitas Bali Dwipa, 2024)
This study seeks to explore the use of adverbs of manner in Harper Lee's “To Kill a Mockingbird” in an attempt to understand their role in forming the narrative and stylistic effects of the novel. The data source is the first edition of the novel, Lee, 1960. A chapter purposively sampled from the beginning, middle, and the end of the book was selected for analysis. Identification and subsequent classification of all the adverb manner instances in these chapters by their semantic categories and syntactic positions were carried out. The analysis showed that Lee used many adverbs of manner (N =127), with Adverbs of Degree being the most frequent category followed by a very diverse range of other adverbs. The most frequent position of adverbs of manner was pre-verb. These findings suggest that Lee uses adverbs of manner purposefully to contribute to character development, atmosphere, and the exploration of key themes in the novel. The present study offers an insight into stylistic effects created by the adverbs of manner in the literary text and has implications for language teaching and literary analysis.